(5x-2)(3x+4)=(3x-5)(5x+1)+15

Simple and best practice solution for (5x-2)(3x+4)=(3x-5)(5x+1)+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-2)(3x+4)=(3x-5)(5x+1)+15 equation:


Simplifying
(5x + -2)(3x + 4) = (3x + -5)(5x + 1) + 15

Reorder the terms:
(-2 + 5x)(3x + 4) = (3x + -5)(5x + 1) + 15

Reorder the terms:
(-2 + 5x)(4 + 3x) = (3x + -5)(5x + 1) + 15

Multiply (-2 + 5x) * (4 + 3x)
(-2(4 + 3x) + 5x * (4 + 3x)) = (3x + -5)(5x + 1) + 15
((4 * -2 + 3x * -2) + 5x * (4 + 3x)) = (3x + -5)(5x + 1) + 15
((-8 + -6x) + 5x * (4 + 3x)) = (3x + -5)(5x + 1) + 15
(-8 + -6x + (4 * 5x + 3x * 5x)) = (3x + -5)(5x + 1) + 15
(-8 + -6x + (20x + 15x2)) = (3x + -5)(5x + 1) + 15

Combine like terms: -6x + 20x = 14x
(-8 + 14x + 15x2) = (3x + -5)(5x + 1) + 15

Reorder the terms:
-8 + 14x + 15x2 = (-5 + 3x)(5x + 1) + 15

Reorder the terms:
-8 + 14x + 15x2 = (-5 + 3x)(1 + 5x) + 15

Multiply (-5 + 3x) * (1 + 5x)
-8 + 14x + 15x2 = (-5(1 + 5x) + 3x * (1 + 5x)) + 15
-8 + 14x + 15x2 = ((1 * -5 + 5x * -5) + 3x * (1 + 5x)) + 15
-8 + 14x + 15x2 = ((-5 + -25x) + 3x * (1 + 5x)) + 15
-8 + 14x + 15x2 = (-5 + -25x + (1 * 3x + 5x * 3x)) + 15
-8 + 14x + 15x2 = (-5 + -25x + (3x + 15x2)) + 15

Combine like terms: -25x + 3x = -22x
-8 + 14x + 15x2 = (-5 + -22x + 15x2) + 15

Reorder the terms:
-8 + 14x + 15x2 = -5 + 15 + -22x + 15x2

Combine like terms: -5 + 15 = 10
-8 + 14x + 15x2 = 10 + -22x + 15x2

Add '-15x2' to each side of the equation.
-8 + 14x + 15x2 + -15x2 = 10 + -22x + 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
-8 + 14x + 0 = 10 + -22x + 15x2 + -15x2
-8 + 14x = 10 + -22x + 15x2 + -15x2

Combine like terms: 15x2 + -15x2 = 0
-8 + 14x = 10 + -22x + 0
-8 + 14x = 10 + -22x

Solving
-8 + 14x = 10 + -22x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22x' to each side of the equation.
-8 + 14x + 22x = 10 + -22x + 22x

Combine like terms: 14x + 22x = 36x
-8 + 36x = 10 + -22x + 22x

Combine like terms: -22x + 22x = 0
-8 + 36x = 10 + 0
-8 + 36x = 10

Add '8' to each side of the equation.
-8 + 8 + 36x = 10 + 8

Combine like terms: -8 + 8 = 0
0 + 36x = 10 + 8
36x = 10 + 8

Combine like terms: 10 + 8 = 18
36x = 18

Divide each side by '36'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 4x+152=6x+166 | | 4k^2+3k-7=0 | | 9p+5q-2p= | | X-3+8=20 | | 3p+9=6p | | 5x-4+3=19 | | 5b-12b-90= | | 4k^2+11k+7=0 | | -7-3k=-4k | | 7j+4j+7k= | | -4t-7t= | | 360=x+7+2x-1 | | 4x+8=9x-7 | | 1/7-t/7=-5/7 | | -2(18-3x)=7y+2y | | 180=x+5+x+6+x+7 | | 9-6*x=-15 | | 18p=8 | | 75(2x-3)-1=5 | | 5g+6=51 | | 41=-4-(5x) | | 12+c=24 | | 10x+14x=10-4 | | m-18=36 | | 4(3x-2)+2(3x+3)=3x+28 | | 5a+10b-4a-7b= | | x^4*x^7= | | k=14 | | -(1x+4)=-3x | | 4(a-15)=64 | | 14n+12p+4n+12p= | | 3x-y(5-x)=7 |

Equations solver categories